How to Record the Allocations of Special Drawing Rights in Government Finance Statistics. (Technical Notes and Manuals; Technical Notes and Manuals, 2022)
This note provides statistical guidance to IMF staff and country authorities on the recording of the 2021 general allocation of Special Drawing Rights (SDRs) in the government finance statistics (GFS), which is also applicable to previous SDR allocations. SDR allocations received by members are recorded as a liability in the form of SDR allocations vis-a-vis the SDR Department of the IMF, which is part of gross debt of the public sector unit (Ministry of Finance/Treasury or central bank or other publicly controlled entity) on whose balance sheet SDRs are recorded, with a corresponding entry for SDR holdings as a financial asset. No transfer of wealth occurs due to the SDR allocation. It should be stressed that the statistical guidelines do not specify on whose balance sheet SDR holdings and allocations should be recorded, as this decision is determined by the member's domestic legal and institutional arrangements.